ANALISIS RESIKO CEMARAN Pb AKIBAT ASAP PABRIK TERHADAP KESEHATAN PEKERJA DAN MASYARAKAT SEKITAR ( Studi Kasus : PT. Inti General Yaja Steel, Semarang-Jawa Tengah) - Herti Ayu Yusvalina (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
PT. Inti General Yaja Steel is one of the industry's largest and oldest steel foundries in Semarang, Central Java. Industrial processes PT. Inti General Yaja Steel contained fuel use (fossil) so there is output in the form of air emissions. Emitted high enough in the production process is one of them is lead (Pb) and if not handled skillfully can pollute the environment and affected the health of workers and surrounding communities. Studies on air contamination risk analysis is required as a result of factory smoke surrounding air quality monitoring efforts and the health of workers and communities around the plant. There are 4 steps in determining the risk analysis i.e hazard identification, exposure assessment, dose-response assessment and risk characteristics. There are 4 locations used for the sampling location. All the calculated Pb concentration is far below the quality standard in accordance Central Java Governor Decree No. 8 In 2001 the Pb = 2 μg/m3. The maximum intake obtained is 0.002904 mg / kg.day and intake of the respondents are still far below the standard. Estimated value of the risk is still below the maximum risk = 1 at 3.1 x10-5. based on the above it can be seen that the area around the PT. General Yaja Steel core is still safe and not harm the health of workers and surrounding communities.